Hourly scheduling of thermal units utilizing an innovative hybrid approach - Vempalle Rafi; Shaik Hussain Vali; Sadhu Radha Krishna; Uppuluri Suryavalli; M. Rajesh; Sayapogu Prateepkumar (Institute of Advanced Engineering and Science, 2026)
The producing unit must be turned on at a time that meets the power system network's needs. It also determines the order of unit shutdowns based on cost. Unit commitment includes computation and turning units on and off. Committed units are planned to join the power system network. The combinatorial character of unit commitment makes it a crucial research issue and optimization job in contemporary power system. In order to effectively use the available resources and equalize the load demand on an hourly basis, unit commitment might be used. In order to solve an optimization issue involving unit commitment, this work introduces a new hybrid approach that combines a whale optimization algorithm (WOA) with a self-organizing migration algorithm (SOMA). An important part of any migration loop is the WOA technique, which is used to evaluate the optimum strength population from the populations that are created stochastically. The suggested hybrid approach is evaluated using two test systems. Before moving on to the IEEE 39 bus system, a four-unit system is implemented. The efficiency of the suggested hybrid WAOSOMA is addressed by comparing the generated simulation results with approaches found in the literature.